#1**+2 **

We are using these log properties

log a + log b = log(a * b)

log a - log b = log (a /b)

alog b = log b^a

So we have

log x + log y - 2 log z =

log (x * y) - log z^2

log [ (x * y) / z^2 ]

CPhill
Dec 4, 2017

#2**+2 **

I appreciate it!. I really like it when people get together and share ideas. Great website, continue the good work!. Either way, great web and I look forward to seeing it grow over time. Thank you so much. |=>super smash flash 2 |=>bloons tower defense 5

rebeccahickshq
Dec 4, 2017